2004
DOI: 10.1097/01.ccm.0000105305.95815.91
|View full text |Cite
|
Sign up to set email alerts
|

Decreasing unplanned extubations: Utilization of the Penn State Children’s Hospital Sedation Algorithm

Abstract: Utilization of the PSCHSA resulted in a decreased number of unplanned extubations without increasing the length of PICU stay. Implementation of the PSCHSA is needed in other PICUs to validate these findings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
43
0
3

Year Published

2012
2012
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 60 publications
(48 citation statements)
references
References 13 publications
1
43
0
3
Order By: Relevance
“…We found that lack of sedation of infants may contribute to unplanned extubations, which has been shown in PICU studies 13 as well as in other NICUs. Although sedation is a very important factor in PICUs, it is not without its own adverse effects.…”
Section: Discussionmentioning
confidence: 72%
“…We found that lack of sedation of infants may contribute to unplanned extubations, which has been shown in PICU studies 13 as well as in other NICUs. Although sedation is a very important factor in PICUs, it is not without its own adverse effects.…”
Section: Discussionmentioning
confidence: 72%
“…Sedation as a method to minimize agitation was not as studied. On the other hand, there is evidence that a sedation/analgesia protocol significantly reduces the incidence of UE in both pediatric 25 and adult 26 patients.…”
Section: Discussionmentioning
confidence: 99%
“…Although increasing sedation will decrease the risk of unplanned extubations, caution should be exercised in seeking low rates of unplanned extubations by excessive use of sedatives and neuromuscular blockers, which in turn can result in worse patient outcomes. Sedation algorithms (such as the Penn State Children's Hospital sedation algorithm) 13 or targeted sedation regimens (such as the RESTORE trial) 14 have the potential to balance the risk and benefits; however, whether their utilization will decrease the risk of unplanned extubations but not increase ventilator duration remains to be validated in independent studies. Use of restraints did not lead to any decrease in unplanned extubations in our project.…”
Section: Discussionmentioning
confidence: 99%